EVALUATION OF CYTOKINE IL-6 PROFILE IN PATIENTS HOSPITALIZED WITH COVID-19 IN THE 15TH REGIONAL HEALTH OF PARANA - Brenda Barroso Pelegrini; Fernanda Ferreira Evangelista; Felipe Aparecido Lacerda de Andrade; Letícia Nishi; Cristiane Maria Colli; Willian Costa Ferreira; Priscilla de Laet Santana (Arquivos do Mudi, 2023)
COVID-19 is a viral infection caused by SARS-CoV-2 coronavirus, discovered in Wuhan,China, in 2019. It is a potentially serious disease with high transmissibility, characterized byworsening due to the exacerbated immune response, coordinated from pro-inflammatorycytokines signaling, leading to tissue damage. Objective: to evaluate the immunologicalprofile of patients affected by COVID-19 through protein measurement that modulatesimmune response and has a great influence on cytokine storms. Materials and methods: theserum concentration analysis of the cytokine IL-6 was performed in patients with the disease.This procedure was developed through the duplicate capture ELISA technique, followingmanufacturer's standards, with the serum used from University Hospital of Maringa (HUM)patients who were hospitalized in the ward (G2), and who were in the intensive care unit butdied (G3), as well as negative samples for COVID-19 (G1-control) from blood donors storedin the Maringa Regional Blood Center. Data were analyzed using GraphPad Prism software,version 7.0. Results: an increase in IL-6 was observed in more severe patients (G3).Conclusion: the cytokine IL-6 has been shown to be important prognostic markers ofworsening of COVID-19.